Behind the Skyscrapers: An Assessment of Dubai’s Cultural and Creative Scene - Marieh Mustafa Sharaf (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Dubai has witnessed an upsurge of creative and cultural initiatives within the years of 2020 and 2021 with strong plans and strategies of becoming the hub of creative economy in the coming years. This research traces the arts, culture, and creativity within the city to produce a comprehensive timeline and an assessment of the repository of its physical manifestations in the city. Focusing on three main districts: Dubai Historical District, Al Serkal Avenue, and Dubai Design District, the narrative of arts and gentrification are explored in relation to governance, urban development, and social life. The findings reflect on the path of culture and creativity in Dubai’s urban fabric and explores the resilience of its network in relation to factors such as community engagement, financial risks, tourist activity, and global changes to assess best practices and envisage a plan of action for the new strategies put forth.